The experiences of living with a stuttering disorder across the lifespan : psychosocial impact and acceptance and commitment therapy - Beilby, Janet Maude (Curtin University, 2013)
In recent stuttering disorders research, increasing importance has been placed on viewing the disorder from a multidimensional perspective. Researchers have shown how the impact of the disorder reaches far beyond the surface speech components. There have been demonstrated psychosocial and anxiety effects for the person living with a stutter which underpins the value of taking a more comprehensive view of this complex problem. Concurrently, there has been research in allied speech and language areas addressing the impact of communication difficulties not only on the person themselves but on family members with whom they share daily life.The primary aim of this thesis was to explore the experiences of living with a stuttering disorder across the lifespan. The aim was to do this by investigating the impact of the disorder on the individual (child, adolescent and adult), and on their family members (siblings, parents and partners). The context of the thesis presents this impact on a number of different planes including behavioural and social difficulties, self-awareness of stuttering, reactions to stuttering, communication difficulties in daily situations, and overall quality of life. The impact on the relationships the person who stutters shares with intimate others is also disclosed.An overview of stuttering across the lifespan in the first two papers is discussed in terms of the impact of a stuttering disorder on children and adolescents living in Western Australia. A comparison is drawn between the reactions and experiences of individuals who stutter to those of people who do not stutter. Significant levels of adverse impact as a result of living with a stutter are described.The next two papers in the thesis present the impact of the stuttering disorder on the parents and siblings of children who stutter. These papers describe the relationship between siblings, the impact on the fluent sibling and the impact on the parent-child relationship. Significant findings pertaining to lack of attachment and trust between the young people and their parents emerged. The responsibilities and demands on parents and siblings in the family context are highlighted.The focus of the fifth paper is the experience of living with a person who stutters from the perspective of their life partner. This paper explores perceived quality of life with unexpected differences unfolding between the quality of life experienced by the adult who stutters and their partner's perceptions of this experience. Apprehensions and demands around emotional support, social interactions, communication dependencies and therapy support are described.In the context of the overall findings from the preceding five lifespan impact papers, the sixth paper proposes an overview of a holistic Acceptance and Commitment Therapy (ACT) for the treatment of stuttering disorders in adults. The positioning of ACT as a novel and valid treatment for stuttering disorders is discussed and the unique platform from which the potential for this treatment to produce fluency gains and psychosocial outcome improvements is described. Finally, the seventh paper investigates the effectiveness of an ACT group intervention program for adults who stutter. Significant results and clinical research support are presented in terms of improvements in psychosocial functioning, readiness for therapy and change, utilisation of mindfulness skills and psychological flexibility, and improved frequency of stuttering as a result of this preliminary ACT treatment programme.This thesis documents the impact of stuttering and proposes an original approach to the resolution of impact through intervention for the demonstrated psychosocial concerns of the individual and their immediate family members.